Study on the Material Performance of Ceramsite Concrete Roof Brick. (2017) - Han, Rubing; xu, Zhimao; Qing, Yutao
Abstract: In order to study the feasibility of the ceramsite concrete applied in energy saving renovation of existing buildings roof, we use three kinds of different particle sizes of ceramsite, including big (diameter 15-18mm), middle(diameter is 6-9mm) and little (diameter 3-5mm) particles, river sand, and concrete, with the same ratio, to make bricks for studying the physical properties and mechanical properties. Implement research on roof insulation performance of water storage roof bricks made by ceramsite concrete in existing buildings through the experimental test of water storage bricks. The results show that the big particles provide the best anti-pressure performance, lowest thermal conductivity, and lowest dry density, thus the performance is best. Using water storage bricks made from ceramsite concrete in the energy-saving reconstruction of existing buildings roof effect is well, and the maximum temperature difference is up to 27.1 degrees compared with common roof.